Independence of Sports Clubs in the United Arab Emirates (Football Companies as an Example) - Al-Tamimi, Nasser Mohamed Ali Mohamed; Baaziz, Mohamed; Mrayeh, Maher (Advances in Social Sciences Research Journal, 2024)
Investment in the field of sports is considered one of the most important investments, as it plays a major role in the economic development of countries and achieving successive successes attracts multiple foreign capital. Sports investment also plays an important role in the economies of countries due to its importance in attracting local and foreign investments, and its role in hosting major sporting events in countries. The idea of establishing sports companies began with the process of implementing professionalism in the nineties of the last century. Therefore, this study addresses the independence of sports clubs in the United Arab Emirates, by explaining the importance of sport, its role in investment, and its importance in the national economy, and reviewing the experience of the United Arab Emirates in with a case study of Al Ain Football Club in the United Arab Emirates before and after its conversion. To a football sports company, by explaining the concept of sports clubs and explaining the most important concepts related to the subject of the study, as well as clarifying the privatization of football sports clubs and the advantages of this privatization, as well as its negatives, and the most important risks facing the privatization of sports clubs. The study aimed to identify the obstacles to the independence of sports clubs, The researcher used the research sample by using a questionnaire form as a means of collecting data and analyzing the results to reach the most important results of the study, while including the study with many recommendations at the conclusion of the study.